2019
DOI: 10.1002/mren.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis, Characterization, and Flow Properties of Ethylene–Diene Copolymers

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/mren.201800071. Ethylene Diene TerpolymersThe flow response of branched entangled resins is dominated by the branching topology of the constituent molecules, a property that is not directly accessible using experimental analytical tools for industrially relevant complex resins. In this paper, the controlled terpolymerization of ethylene, 1,9-decadiene, and either hexene or octene in a continuous stir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Yet, because of the radical mechanisms involved in these treatments, ample control over LCB formation is rather impossible; hence, polymers with complex structures are obtained in those cases. In-reactor technologies such as copolymerization of ethylene with either in situ-formed or previously isolated macromonomers, , or with a nonconjugated α,ω-diene have also been developed. Nevertheless, only a limited number of catalyst systems have been shown to efficiently generate and incorporate macromonomers, while the second approach is limited by the rather scarce availability of α,ω-dienes and by the uneven distribution of LCB in the final polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, because of the radical mechanisms involved in these treatments, ample control over LCB formation is rather impossible; hence, polymers with complex structures are obtained in those cases. In-reactor technologies such as copolymerization of ethylene with either in situ-formed or previously isolated macromonomers, , or with a nonconjugated α,ω-diene have also been developed. Nevertheless, only a limited number of catalyst systems have been shown to efficiently generate and incorporate macromonomers, while the second approach is limited by the rather scarce availability of α,ω-dienes and by the uneven distribution of LCB in the final polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HDPE resins made by Cr catalysts, which are major PE products by these catalysts, are usually claimed to be with LCB structure despite the fact that its amounts are often inadequate to allow the resins to be readily used in extensional flow-critical application settings . With metalloene/nonmetallocene catalysts, macromonomer incorporation becomes a more convenient, more efficient pathway accessing LCB structure for PE, as a variety of metallocene and late-transition metal catalysts are found to be capable of generating macromonomers, which, after being in situ or ex situ incorporated into the polymer chain, lead to formation of LCB structure. One prominent example is constrained geometry catalyst (CGC, such as Dow Chemical’s [(C 5 Me 4 )­SiMe 2 N­( t -Bu)]­TiCl 2 ) systems that directly synthesize in polymerization long-chain branched ethylene homopolymers (HDPE) and ethylene/high α-olefin random copolymers (ranging from LLDPE to polyolefin elastomers). Metallocene catalysts with controlled comonomer incorporation capability also allow ethylene/nonconjugated α,ω-diolefin (such as 1,9-decadiene) copolymerization to proceed along formation of LCB structure, which further broadens the envelope of LCB-PE synthesis by this advanced catalyst system. …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of molecular hydrogen (H 2 ) for control of polymer molecular weights has the collateral effect of suppressing the terminal vinyl group formation and thus inhibits the occurrence of long chain-branching . An effective solution for that is copolymerization with linear nonconjugated α,ω-diolefin, such as 1,9-decadiene, which increases the vinyl group concentration and synthesizes long chain-branched PE with concomitant control of molecular weight and long chain-branching structure. …”
Section: Introductionmentioning
confidence: 99%
“…In this paper, an attempt of using 1,9-decadiene to prompt long chain-branching structure formation in ethylene polymerization with Ziegler–Natta catalyst is reported (Figure ). 1,9-Decadiene has been widely used in ethylene and propylene polymerization with metallocene catalysts, eliminating the cyclization tendency that as a major side reaction reduces the LCB efficiency of a nonconjugated α,ω-diolefin. In a recent report, we assessed the synthesis of long chain-branched polypropylene through 1,9-decadiene/propylene copolymerization with Ziegler–Natta catalysts, which was specifically tasked to a MgCl 2 /9,9-bis-(methoxymethyl)­fluorine/TiCl 4 catalyst with triethylaluminium (TEA) as a cocatalyst that has long been known as a higher α-olefin-capable Ziegler–Natta catalyst system. The results nevertheless indicated that the catalyst system exhibited a poor incorporation efficiency for 1,9-decadiene, with meaningful incorporations being realized only at greatly increased concentrations, and that the formation of LCB structure was much delayed relative to 1,9-decadiene incorporation, making the synthesis of gel-free LCB-PP rather difficult.…”
Section: Introductionmentioning
confidence: 99%